2019
DOI: 10.24275/rmiq/alim588
|View full text |Cite
|
Sign up to set email alerts
|

REFRIGERATED STORAGE OF HIGH HYDROSTATIC PRESSURE (HHP) TREATED PITAYA (Stenocereus pruinosus) JUICE

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…However, HHP treated samples still exhibited stable sensory qualities at day 14, and showed a slight decrease at day 20. Quiroz-Gonzalez et al (2020) also reported that the sensorial acceptability of pitaya juice was not affected by HHP treatment during 60 days of storage.…”
Section: Sensory Qualitymentioning
confidence: 94%
“…However, HHP treated samples still exhibited stable sensory qualities at day 14, and showed a slight decrease at day 20. Quiroz-Gonzalez et al (2020) also reported that the sensorial acceptability of pitaya juice was not affected by HHP treatment during 60 days of storage.…”
Section: Sensory Qualitymentioning
confidence: 94%
“…In pitaya juice [ 140 ], after 45 days storage, a 10% decrease of total phenolic content was observed in HPP juice. Ascorbic acid (AA) in untreated juices showed a significant reduction (9%) after 15 days, while in HPP-treated juices the decrease reached up to 6% after 30 days ( Table 2 ).…”
Section: Impact Of Hpp On Antioxidant Activity During Storage Of Fruits and Fruit Productsmentioning
confidence: 99%
“… Phenolic compounds were not affected by HPP but had a 10% decrease after storage. Betaxanthins showed no significant changes during storage (21.1 to 18.9 mg/g), while betacyanins showed a 28% reduction [ 140 ] Red grapefruit juice HPP: 550 MPa, 10 min, 25 °C TP: 110 °C, 8.6 s Storage: 30 days, 4 °C DPPH (mmoles Trolox/L) FRAP (mmoles Trolox/L) TPC: Folin-Ciocalteu (mg GAE/100 g) Ascorbic acid: HPLC-UV-vis (mg/100 mL) Antioxidant activity decreased by 1.4% (DPPH) and 8.5 % (FRAP) after TP; no change with unprocessed samples during storage. DPPH and FRAP was decreased by 5.0 and 14.3% in HPP-treated grapefruit juice and 5.3 and 12.8% in TP-treated grapefruit juice during total storage, respectively.…”
Section: Impact Of Hpp On Antioxidant Activity During Storage Of Fruits and Fruit Productsmentioning
confidence: 99%
“…According to the pH values found for these pulps (Table 1), they are classified as acid or medium acid foods (3.7 < pH < 4.5) (Ramaswamy & Abbatemarco, 1996), Decrement of aerobic mesophilic count was observed during refrigerated (4°C) storage of pitaya juice as from the 35th day of the cool storage (Quiroz-González et al 2020;García-Mateos et al, 2019).…”
Section: Microbiological Analysesmentioning
confidence: 99%